"Too many cooperatives and too few cooperativists": the consumer cooperative movement in Catalonia 1898–1939. Issue 2 (4th May 2022) - Garner, Jason
ABSTRACT: This article charts the evolution of the Catalan Cooperative movement from the creation of the first regional organisation, the Chamber of Catalan and Balearic Cooperatives in 1898, to the end of the Civil War in 1939. It looks at the aims of the Chamber and its successor organisation the Federation of Catalan Cooperatives, as expressed at congresses and in the movement's press and then analyses the tactics adopted to achieve these and why, in general, they did not enjoy the success that was hoped for. The founders of the Chamber were influenced by movements in other countries, specifically France, Belgium and the United Kingdom and was a member of the International Cooperative Alliance adopting the principles of these including political neutrality and the belief in acting independently of the State and political organisations. It was hoped that Catalan cooperatives would be able to catch up with and match the strength and influence of cooperatives in these countries. However, although the cooperative movement enjoyed spectacular growth during the Civil War, much of the progress that was made by cooperatives was due to circumstance and state intervention rather than due to the movement itself.